Healing of a Large Periapical Lesion and Adjacent Cortical Bone: Cone-Beam CT Aided Diagnosis and Treatment - Gulsahi, Kamran (The Journal of Dentists, 2018)
The primary aim of root canal treatment is the resolution of clinical symptoms and radiographic signs. Periapical lesion is a crucial problem resulting in the loss of teeth. The major reason of periapical lesion associated with infected pulpal tissue are caused by pulpal inflammation and/or degeneration through deep caries, trauma, or by a combination of these parameters. Periapical lesion in teeth with root canal treatment should be initially treated with nonsurgical retreatment procedures. Small volume Cone Beam CT can be a powerful tool in endodontic diagnosis, treatment planning and follow-up. This case report presents a complete clinical and radiological healing of a large periapical lesion and adjacent cortical bone of a hopeless tooth after retreatment procedures.